briks123 wrote:

Just to expand on the explanation.

x+y=120 means x=120-y

y+z=160 means z=160-y

Thus, z-x=(160-y)-(120-y)=40-y+y=40

Doh! In the absence of multiplication, my feeble eyes discarded the brackets, and I came to the same answer by the wrong route (finding x, y and z).

Substituting equations:

\(z-x = 40-2y; y = 160-z\)

\(z+x = 280\)

Combining equations:

\((x+y)/2 + (y+z)/2 = 140\)

\(2y+x+z = 280\)

Compare scribbles:

\(y = 0; z = 160; x = 120\)

\(z-x = 40\)

If, like me, you find yourself wandering down the dark tunnel... there can still be luck. I didn't finish the section on time though